Kualitas Pelayanan Kesehatan dan Vasiknasi Covid-19 di Puskesmas Rao Kabupaten Pasaman - Fitri Hartati; Dasman Lanin (PUBLICNESS: Journal of Public Administration studies, 2022)
The purpose of this study is first, to describe the quality of health services at Rao Health Center in terms of reliability, tangibles, responsiveness, assurance and empathy. Second purpose is to describe the quality of the Covid-19 vaccination service at the Rao Health Center in terms of reliability, tangibles, responsiveness, assurance and empathy. This research used a semi-qualitative research commonly called mixed research. The data in this study was collected by using both of interviews and documentation. Data was analyzed by using data reduction, data presentation and conclusion drawing (evidence). Based on the results of the study, it can be concluded that the quality of health services and Covid-19 vaccination services at Rao Health Center has not been optimal in its implementation and the response of health workers at Rao Health Center in serving patients has not met patient expectations.